(untitled) (Biuletyn Kryminologiczny, 2015)
The incidence rate of domestic violence cases in Europe has not really significantly decreased in the last ten years, and Spain is not an exception on this. Despite legislative changes and improvements that have taken place in many of our countries regarding penal punishment of those behaviors, it seems to be not enough or perhaps not suitable for all possible cases in this field. For this reason, for some time it is being discussed and, in any cases, trying out with the option to apply other techniques of conflict resolution based on restorative justice (and specifically the process of mediation between victim and offender). The purpose of this brief paper is then to examine the current legal situation in Spain about mediation in cases of domestic violence, and the opinions that have been expressed on this from the criminal doctrine.